2012
DOI: 10.1152/jn.00652.2011
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive coding is constrained to midline locations in a spatial listening task

Abstract: Although such adaptation is thought to improve coding of relevant stimulus features, the relationship between adaptation at the neural and behavioral levels remains to be established. Here we describe improved discrimination performance for an auditory spatial cue (interaural time differences, ITDs) following adaptation to stimulus statistics. Physiological recordings in the midbrain of anesthetized guinea pigs and measurement of discrimination performance in humans both demonstrate improved coding of the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 53 publications
6
28
0
Order By: Relevance
“…One mechanism for adapting to the presence of an earplug in one ear would be to adjust the sensitivity of auditory neurons to binaural localization cues. Recent studies have shown that the sensitivity of IC neurons to interaural level differences (ILDs; Dahmen et al, 2010) and interaural time differences (ITDs; Maier et al, 2012) can change following short-term adaptation to stimulus statistics, and, as previously illustrated (Figure 8), cortical cooling can produce pronounced alterations in collicular firing-rate-ILD functions. Behavioral evidence, however, suggests that adaptation to a conductive hearing loss in one ear takes place by learning to reweight different localization cues in favor of the monaural spectral localization cues provided by the non-occluded ear rather than by remapping the altered binaural cues (Kacelnik et al, 2006; Kumpik et al, 2010).…”
Section: Corticofugal Modulation and Auditory Plasticitymentioning
confidence: 84%
“…One mechanism for adapting to the presence of an earplug in one ear would be to adjust the sensitivity of auditory neurons to binaural localization cues. Recent studies have shown that the sensitivity of IC neurons to interaural level differences (ILDs; Dahmen et al, 2010) and interaural time differences (ITDs; Maier et al, 2012) can change following short-term adaptation to stimulus statistics, and, as previously illustrated (Figure 8), cortical cooling can produce pronounced alterations in collicular firing-rate-ILD functions. Behavioral evidence, however, suggests that adaptation to a conductive hearing loss in one ear takes place by learning to reweight different localization cues in favor of the monaural spectral localization cues provided by the non-occluded ear rather than by remapping the altered binaural cues (Kacelnik et al, 2006; Kumpik et al, 2010).…”
Section: Corticofugal Modulation and Auditory Plasticitymentioning
confidence: 84%
“…The best coding resolution, i.e., the most information, is found in this steeper region [30]. Intensity and ITD response functions have been shown to shift as result of adapting to stimulus statistics [31, 32]. Such shifts of nonlinear response functions change the operating point, resulting in larger differences in neural firing rates.…”
Section: Discussionmentioning
confidence: 99%
“…These coincide normally with locations directly in front (Stecker et al, 2005). In the subcortical neurons described in these previous studies, the slope of the tuning curve tended to approach the location from which the majority of sounds originated (Dahmen et al, 2010; Maier et al, 2012). Thereby, these neurons shift their best discrimination ability toward the direction in which most of the sound sources reside.…”
Section: Discussionmentioning
confidence: 79%
“…However, recent animal studies have described an alternative mechanisms through which the population rate code might be able to target better selectivity to specific spatial locations. This has been described in subcortical auditory neurons as an adaptation mechanism to stimulation statistics (Dahmen et al, 2010; Maier et al, 2012). In the wide spatial tuning curves, the best discrimination power between sound source locations is provided by the steepest parts of the slopes.…”
Section: Discussionmentioning
confidence: 91%